Preservation of wild feline semen by freeze-drying: experimental model - Magalhaes, L. C. O.; Melo-Ona, C. M.; Sudano, M. J.; Paschoal, D. M.; Crocomo, L. F.; Ackermann, C. L.; Landim-Alvarenga, F. C.; Lopes, Maria Denise [UNESP] (Brazilian Coll Animal Reproduction, 2012)
According to the Convention on International Trade in Endangered Species, 36 wild feline species are threatened by extinction or severely endangered, and to save them is the target of several conservation programs. This study aimed to assess the viability of the freeze-drying technique for domestic cat sperm cells, with the ultimate goal of transferring this technology to the wild feline species. The domestic cat is an excellent experimental model for wild felids. It is in this scenario that the freeze-drying process (low-temperature vacuum dehydration) of sperm cells shows its value in preserving male cats' germplasm. Results from membrane and DNA integrity analysis are promising and validates the use of frozen-dried sperm samples in intracytoplasmic sperm injections (ICSIs). Further studies are still necessary to evaluate the ICSI embryo production using domestic cat frozen-dried sperm and the possibility of using such technology with wild felines.